A narrative study of the experience of feedback on a professional doctorate: 'a kind of flowing conversation'. Issue 2 (4th May 2019) - Adams, Gill
ABSTRACT: Feedback has an important role in supporting learning. It is through feedback that learners can actively construct and clarify understanding, monitor their performance and direct their learning. Despite attention on feedback in higher education, limited research exists exploring the role and experience of feedback within doctoral programmes. This article focuses on student experiences of feedback during a professional doctorate in England. Analysis of the narrative of one recent Doctorate in Education graduate reveals several inter-related themes, illustrating the role of peers in supporting the move to autonomous researcher. This intensive focus on one student's experience narrative contributes to a reconceptualization of feedback as dialogic, revealing feedback through the doctoral journey as an ongoing dialogue, with the doctoral researcher taking increasing responsibility for orchestrating the conversation. I argue that such a perspective moves beyond the traditional view of doctoral learning through the support of a supervisor to encompass both formal and informal learning experiences within a community of research practice, emphasising the active participation of the doctoral candidate in this community. I discuss the potential contribution of student experience stories to the development of doctoral relationships and practice.